IMPLEMENTATION OF PALEMBANG MALAY CULTURAL VALUES IN THE SUSTAINABILITY OF PALEMBANG PEMPEK ENTERPRISES (ETHNOGRAPHIC STUDY OF PEMPEK ENTREPRENEURSHIP IN PALEMBANG) - Atika Khairunnisa; Yuhendri L V (Journal of Global Business and Management Review, 2026)
Business sustainability is not solely determined by economic capability, but also by the cultural values embedded within society. In Palembang City, the pempek business represents a traditional culinary sector that continues to survive because of the strong influence of Palembang Malay culture in daily business activities. This research was conducted to explore the role of cultural values in preserving the continuity of pempek enterprises.This research employed a qualitative ethnographic approach. Data were gathered through field observations, comprehensive interviews, and documentation. Twelve informants participated in the study, including cultural leaders, business owners, workers, family members, and consumers from Pempek Sentosa, Pempek Koyek, and Pempek Minah. The analysis process involved reducing data, organizing information, and drawing conclusions interactively. The results reveal that several Palembang Malay values are strongly embedded in pempek businesses, such as honesty, friendliness, politeness, discipline, cleanliness, responsibility, cooperation, family solidarity, and religious commitment. These values are demonstrated through ethical customer service, transparent business transactions, teamwork among employees, family-based business management, and efforts to maintain product quality and halal standards.The presence of these cultural principles has proven beneficial for business continuity because they help establish consumer trust, strengthen customer loyalty, improve operational effectiveness, and preserve local cultural uniqueness. Therefore, Palembang Malay culture serves not only as a regional identity but also as a powerful social asset that reinforces the endurance of traditional culinary businesses.